SYNTHESIS OF NEW 2-(2,4-DIMETHOXYPHENYL) -1,3,4- OXADIAZOLES AND THEIR ANTIMICROBIAL ACTIVITY - K. P. HARISH; K. N. MOHANA (International Journal of Pharma and Bio Sciences, 2013)
A series of new 2-(2,4-dimethoxyphenyl)-1,3,4-oxadiazole derivatives, 4(a-m) were synthesized by using 2,4-dimethoxybenzoic acid (1) as starting material. Different spectral data were used to characterize the newly synthesized compounds. All the compounds were screened for their in vitro antimicrobial activity. The results indicated that some of the compounds showed potential activity and comparable to those of commercial antibiotics. Few compounds showed good antimicrobial activity against tested strains.